Autonomia da vontade e interesse moral em Kant - Botton, Alexandre Mariotto (2005)
The principal objective of this dissertation was to analyze the concepts of autonomous will and interest in the of Kant and based on his system of ethics. Our principal source of research are Kant s own books, especially Fundamentals of metaphysics and customs (FMC), Critic of Pratical Reason (CRPr) and some parts of Critic of Pure Reason (CRP), first we analyzed , from FMC, the concept of liberty and principally practical liberty. However, we perceive that in CRPr Kant arrives at only a negative notion of liberty, that is, how free will is independent of sensibility. Then we write about the concepts of will and duty in FMC and from them we see how Kant arrives at the notion of autonomous will that serves as positive concept of liberty and consequently as the supreme principal of morality. However, this principle is incompatible with acting by interest which it becomes necessary to investigate how man can take interest in morality without , however, by interest. We analyze then the concept of autonomous will with the idea of knowing how it can be valid independent of any interest. We conclude that according to Kant moral law imposes itself on human conscious as a fact, the only pure fact, a priori, denominated factum of reason . We retake the concept of interest from the perspective that this can be founded on autonomy. Finally, we observe that de feeling of respect is a valid consequence of moral law for rational and sensitive beings. Thus, we conclude that without doubt man takes interest in moral law exactly because since it s not at the service of any particular interest it reveals a maximum interest of reason and its amplification of its use.